The art of Pirates of the Caribbean : on stranger tides - Singer, Michael, 1952-; Bruckheimer, Jerry; Disney (Firm). (New York : Disney Editions, 2011)
Working drawings and sketches by Disney artists for the movies in the Pirates of the Caribbean series, The curse of the Black Pearl, Dead man's chest, and At world's end.
'A Welcome book.'
Keywords: Pirates of the Caribbean, on stranger tides (Motion picture) -- Pictorial works; Motion pictures -- Art direction